The role of dopamine signaling in epileptogenesis - Bozzi, Yuri; Borrelli, Emiliana (Frontiers in Cellular Neuroscience, 2013)
Clinical and experimental studies implicate most neuromodulatory systems in epileptogenesis. The dopaminergic system has a seizure-modulating effect that crucially depends on the different subtypes of dopamine (DA) receptors involved and the brain regions in which they are activated. Specifically, DA plays a major role in the control of seizures arising in the limbic system. Studies performed in a wide variety of animal models contributed to illustrate the opposite actions of D1-like and D2-like receptor signaling in limbic epileptogenesis. Indeed, signaling from D1-like receptors is generally pro-epileptogenic, whereas D2-like receptor signaling exerts an anti-epileptogenic effect. However, this view might appear quite simplistic as the complex neuromodulatory action of DA in the control of epileptogenesis likely requires a physiological balance in the activation of circuits modulated by these two major DA receptor subtypes which determines the response to seizure-promoting stimuli. Here we will review recent evidences on the identification of molecules activated by DA transduction pathways in the generation and spread of seizures in the limbic system. We will discuss the intracellular signaling pathways triggered by activation of different DA receptors in relation to their role in limbic epileptogenesis, which lead to the activation of neuronal death/survival cascades. A deep understanding of the signaling pathways involved in epileptogenesis is crucial for the identification of novel targets for the treatment of epilepsy.